2021
DOI: 10.1038/s41598-021-00472-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gender and education on cocaine users in an outpatient cohort in Spain

Abstract: Gender significantly influences sociodemographic, medical, psychiatric and addiction variables in cocaine outpatients. Educational level may be a protective factor showing less severe addictive disorders, longer abstinence periods, and better cognitive performance. The aim was to estimate gender-based differences and the influence of educational level on the clinical variables associated with cocaine use disorder (CUD). A total of 300 cocaine-consuming patients undergoing treatments were recruited and assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
0
8
0
3
Order By: Relevance
“…Large samples of women should be included to confirm the sexual dimorphism observed in this study; (2) Some sociodemographic differences were associated with the sources of recruitment for the control and SUD groups. We found significant differences in educational levels between both groups, which could be associated with the appearance and severity of SUD [43]; (3) The recruitment of the sample was conducted from outpatient treatment programs and there are some sociodemographic and clinical variables that remain unknown and could affect the validity of our results (e.g., diet and nutrition, income or economic status, non-psychotropic medication, physical activity); (4) The present data were obtained from patients with a history of SUD in abstinence, and additional experimental groups (e.g., active alcohol and cocaine users) should be included; (5) Longitudinal studies are also needed to monitor changes in LPA concentrations during abstinence at different times in the same abstinent SUD patients; (6) Although we have examined the most abundant LPA species in the human blood, we cannot ignore the presence of other acyl-LPA that were not measured, such as 22:6-LPA, whose relative activity could be relevant; and (7) As we did not measure the expression of precursors (e.g., lysophospholipids and glycerol 3-phosphate (G3P)) and metabolic enzymes involved in the metabolism of LPA (e.g., ATX and lipid phosphate phosphatases (LPP 1-3 )), future research is needed to explore these molecules and elucidate potential differences between healthy controls and patients with SUD.…”
Section: Limitations and Conclusionmentioning
confidence: 72%
“…Large samples of women should be included to confirm the sexual dimorphism observed in this study; (2) Some sociodemographic differences were associated with the sources of recruitment for the control and SUD groups. We found significant differences in educational levels between both groups, which could be associated with the appearance and severity of SUD [43]; (3) The recruitment of the sample was conducted from outpatient treatment programs and there are some sociodemographic and clinical variables that remain unknown and could affect the validity of our results (e.g., diet and nutrition, income or economic status, non-psychotropic medication, physical activity); (4) The present data were obtained from patients with a history of SUD in abstinence, and additional experimental groups (e.g., active alcohol and cocaine users) should be included; (5) Longitudinal studies are also needed to monitor changes in LPA concentrations during abstinence at different times in the same abstinent SUD patients; (6) Although we have examined the most abundant LPA species in the human blood, we cannot ignore the presence of other acyl-LPA that were not measured, such as 22:6-LPA, whose relative activity could be relevant; and (7) As we did not measure the expression of precursors (e.g., lysophospholipids and glycerol 3-phosphate (G3P)) and metabolic enzymes involved in the metabolism of LPA (e.g., ATX and lipid phosphate phosphatases (LPP 1-3 )), future research is needed to explore these molecules and elucidate potential differences between healthy controls and patients with SUD.…”
Section: Limitations and Conclusionmentioning
confidence: 72%
“…98 More females are thought to develop druginduced AAV, largely as a result of the prevalence of thyroid disease in young women, but, interestingly, cocaine/levamisole-associated AAV also shows a female bias 99 despite cocaine use being more prevalent in males. 100 Gender differences also have been seen with medications prescribed for glomerular disease. More females than males are prescribed medication across all illnesses, and adherence to medication is lower in women.…”
Section: Drugsmentioning
confidence: 99%
“…Moreover, a longitudinal study has suggested that an educational level lower than high school and a low job occupation is associated with an increased risk of dementia in alcohol patients [69]. Similarly, our group has recently found that a high educational level could play a protective role in the onset, development, and progression of cocaine use disorders and could also protect against cognitive impairment caused by alcohol consumption throughout life [70,71]. Interestingly, in this study we found a negative association between the state of frontal lobe functions with two signaling molecules, VEGFA and fractalkine, involved in vascular function and neural plasticity.…”
Section: Discussionmentioning
confidence: 66%